Penerapan Terapi Kelompok Terapeutik Dalam Menstimulasi Perkembangan Anak Usia Toddler Dengan Memberdayakan Ibu Dan Kader Kesehatan Jiwa - Wuryaningsih, Emi Wuri; Keliat, Budi Anna; Mustikasari, Mustikasari (Universitas Muhammadiyah Semarang, 2014)
Mental health promotion in toddlerhood has important role to improve of Indonesian human resource quality. This scientific report describes implementation of toddler’s group therapeutic therapy by empowering mother and mental health cadre. The method used is toddler’s group therapeutic therapy in community mental health nursing program. The result showed the therapy could promote the achievement of autonomy in toddlerhood, the mothers’ ability in stimulating the holistic development of the toddlers (motoric, cognitive, language, emotion, personality, morale – spiritual, and psychosocial), and mental health cadre’s ability to help toddler’s family for otonomy development achievement. Mental health nurses in primary health care can implement the group therapeutic therapy by mother and mental health cadre empowerment.